CONTIUBUTION OF ZOOPLANKTON TO THE FISHERY OF DHARAMTAR CREEK, ADJOINING BOMBAY HARBOUR - NAIR., VIJAYALAKSHMI R.; TIWARI, L. R. (Journal of Indian Fisheries Association, 2016)
The rich zooplankton standing stock of Dharamtar creek showed a variation of 8 to 5261 (av .1032) mg C/100 ml/d which led to a turn over of 29 tonnes C/km21y. The estimated fisht-ry potential from zooplankton production was 0.079 tones C/ km2 or 29.00 tonnes/km2/y. The worked out yield in terms of wet weight of fi’ih was 0.059 tonnes /km2 /d. Experimental trawling within the creek showed a potential of 0.19 tonnes /km2 /d suggesting a transfer coefficient of only 31. 4% from secondary to tertiary level. Fish eggs and larvae were very conm10n in the area but contributed collectively only 1% to the total zooplankton population. On an average the outer zone sustained relatively higher population of fJSh eggs and larvae than the interior zone. The mean population density of larvae (334/100 or) was 3.5 times higher than fish eggs ( 93/100 m3)Â suggesting the good survival rate and a congenial environment for larvae to thrive.